The Effect of Bunium persicum (Boiss.) B. Fedtsch. Consumption on Metabolic Syndrome Indices, Muscle Strength, and Cardio-respiratory Function in Active Middle-aged Women: A Randomized Clinical Trial - Maryam Ahmadzadeh; Fatah Moradi; Saman Pashaei (Institue of Medicinal Plants, ACECR, 2019)
Background: The effect of Bunium persicum (Boiss.) B. Fedtsch. on the metabolic syndrome and physical fitness of active people have been less studied. Objective: The purpose of this study was to investigate the effect of B. persicum consumption on metabolic syndrome indices, muscle strength, and cardio-respiratory function in active middle-aged women. Method: The research method was quasi-experimental and 20 active middle-aged women were selected and were randomly divided into two experimental (n=10) and control (n=10) groups. The assessments were carried out in two stages (pre-supplementation and post-supplementation). The duration of supplementation was eight weeks (a 3.5 g B. persicum per day). Subjects' general characteristics, cardio respiratory function, muscular strength, lipid profile, fasting blood sugar, blood pressure, and waist circumference were measured. To analyze the data, two factor analysis of variance with repeated measurements was used at the significant level of P<0.05. Results: B. persicum consumption decreased triglyceride level, while has no significant effects on body weight, body fat percent, body mass index, waist circumference, fasting blood sugar, HDL-c, total cholesterol, systolic blood pressure, diastolic blood pressure, upper body muscle strength, lower body muscle strength, and cardio respiratory function. Conclusion: The consumption of B. persicum for eight weeks and 3.5 g daily improves triglyceride levels in active middle-aged women, but does not seem to have an impact on other indicators of metabolic syndrome and selected components of physical fitness.